Implementasi Sistem Pengelolaan Hotel Berbasis Syariah : Studi Kasus Pada Hotel Syariah Al’Jayri Medan - Nur Aman; Nasution, Salman (Peduli Riset dan Pengabdian Masyarakat, 2022)
This research is a scientific study that discusses the Implementation of Sharia-Based Hotel Management and Service Systems (Case Study at Al’jayri Sharia Hotel Medan). This study aims to find out how the management and service system of the Al’jayri Sharia Hotel Medan and whether the Al’jayri Sharia Hotel management and service system has been implemented in accordance with Islamic Sharia. This research is a qualitative field research by obtaining data or information directly. The data collection prosess is obtained by researchers through documents, interviews, and direct observation. After the data was collected and then processed and analyzed with descriptive analysis, the analysis used to was inductive analysis. This study chose the object of research at the Sharia Hotel Al’jayri Medan which is located at Jl. KH. Wahid Hasyim No. 102. Sei Sikambing D. Kec. Medan Petisah, Medan City, North Sumatera, 20114. The results show that the management system of the Medan Al’jayri Al’jayri Sharia Hotel is in accordance with Islamic Sharia, namely having and using a halal guarantee system, the employees of the Sharia Al’jayri Medan Hotel wear polite clothes covering their genitals. The service system at the Al’jayri Sharia Hotel Medan is implemented properly in accordance with Islamic Sharia, as evidenced by the implementation of basic services, namely selecting guests and cultivating greetings to guests.